Avaliação da associação de miofibroblastos e alterações dos componentes estruturais da matriz extracelular com parâmetros clinicopatológicos de queilite actínica e carcinoma de células escamosas de lábio - Martínez, Farah Essguí Orellana (2021)
Actinic cheilitis (AC) is a potentially malignant disorder of the lip, whose main etiological factor is chronic exposure to ultraviolet (UV) solar radiation. UV radiation can cause genetic and extracellular matrix (ECM) changes that can contribute to the development of lip squamous cell carcinoma (LSCC). In recent years, the study of the cells that make up the tumor microenvironment (TME) has increased considerably, especially myofibroblasts (MFs), due to their role in carcinogenesis. Studies show that MFs are involved in the proliferation and invasion of malignant cells, but it is not yet clear how the changes caused by UV radiation interfere with the behavior of MFs in the process of lip carcinogenesis. Thus, the objective of this research is to evaluate the participation of MFs in lip carcinogenesis, through the correlation of clinical, histological, histomorphometric and immunohistochemical parameters, in ACs and. For this, were used 30 cases of ACs, 31 from the tumor front of LSCC and 14 healthy lips (HLs) that were arranged in blocks and prepared by tissue microarray (TMA) for immunohistochemical reactions (TGF- β, α-SMA and Ki-67) and histochemicals (Hematoxylin and Eosin, Picrosirius Red and Verhoeff Van Gienson). Collection of clinical data and histopathological grading of epithelial dysplasias in ACs were performed using the binary system and the system established by Bryne for LSCC. The areas of solar elastosis in the ACs were analyzed histomorphometrically (degree, extension, depth, and distance to the dysplastic epithelium). The fronts of the LSCCs were analyzed in search of perineural and angiolymphatic invasion. The data were expressed as means and standard deviations, sub mitted to the Kolmogorov-Smirnov test, compared by the Mann-Whitney, Kruskal-Wallis / Dunn tests, and finally correlated in their clinical, histological, immunohistochemical and histomorphometric data by the Spearman test. (SPSS, p <0.05). The analyzes of the ACs showed a greater number of α-SMA + cells in relation to samples of HLs (p = 0.034), and these cells (located in the areas without elastosis) were associated with the vertical expansion of the elastosis itself (p = 0.027). Additionally, it was found that the areas of solar elastosis showed less collagen deposition (p <0.001) and immunostaining for TGF-β (p <0.001), and higher density of elastic fibers (p <0.05), compared with areas without elastosis. Still in ACs, there was a positive correlation between high-risk dysplasias and the proximity of solar elastosis to the dysplastic epithelium (p = 0.027). The analysis of the LSCCs showed a higher number of α-SMA + cells in relation to samples of HLs (p = 0.034), in addition to the reduction in the deposition of total collagen (p = 0.009) and type I collagen (p <0.001) in relation to the ACs and HLs. There was also a negative correlation between the amount of α-SMA + cells and the deposition of total collagen (p = 0.041) and type III collagen (p = 0.041). We also observed that the collagen loss and elastic density was significantly greater in tumors of larger size (p = 0.045) and with nodal metastasis (p = 0.047). Our findings provide evidence of the possible role of myofibroblasts, collagen fibers and areas of elastosis in the process of lip carcinogenesis.